The role of adolescents in stunting prevention: a qualitative study - Mokoagow, Winarsi; Mufdlilah, Mufdlilah; Satriandari, Yekti; Moniz, Maria De Fatima (JHeS (Journal of Health Studies), 2024)
Malnutrition among adolescents is a crucial public health problem and tends to cause serious problems in the next generation, one of which is commonly called stunting. Adolescents As agents of change and prospective parents, adolescents play an important role in stunting prevention. The involvement of adolescents can be one of the important factors in breaking the stunting cycle. This study aims to exxplore deeper into the role of adolescents in stunting prevention efforts. Qualitative research with a phenomenological approach is used in this study. The selection of informants uses purposive sampling. There were 8 adolescent girls as the main informants and one health center nutrition officer as a supporting informant. Data obtaining uses in-depth interviews with an average interview duration of 30-40 minutes. Data analysis uses thematic analysis. There are two themes with four sub-themes, namely the role of adolescents in stunting prevention efforts (three sub-themes: clean and healthy living behavior; adolescent compliance with consuming blood-boosting tablets; adolescent involvement in health activities) and obstacles in stunting prevention efforts (one sub-theme: lack of adolescent knowledge about stunting).Lack of knowledge about stunting among the adolescents in Adow Health Center causes adolescents reluctant to play an active role in preventing stunting issues. An interesting finding is that although adolescents lack knowledge about stunting, they are not interested in seeking information about stunting. Therefore, the development of digital educational content about stunting, especially through social media platforms, is expected to attract the interest of adolescents to increase their knowledge and role in stunting prevention. Further research needs to be carried out, especially on how adolescents use social media to share information and build awareness about stunting issues among their peers.